Halobacterial nano vesicles displaying murine bactericidal permeability-increasing protein rescue mice from lethal endotoxic shock - Balakrishnan, Arjun (Sci Rep, 2016)
Bactericidal/permeability-increasing protein (BPI) had been shown to possess anti-inflammatory and endotoxin neutralizing activity by interacting with LPS of Gram-negative bacteria. The current study examines the feasibility of using murine BPI (mBPI) expressed on halophilic Archaeal gas vesicle nanoparticles (GVNPs) for the treatment of endotoxemia in high-risk patients, using a murine model of D-galactosamine-induced endotoxic shock. Halobacterium sp. NRC-1was used to express the N-terminal 199 amino acid residues of mBPI fused to the GVNP GvpC protein, and bound to the surface of the haloarchaeal GVNPs. Our results indicate that delivery of mBPIN-GVNPs increase the survival rate of mice challenged with lethal concentrations of lipopolysaccharide (LPS) and D-galactosamine. Additionally, the mBPIN-GVNP-treated mice displayed reduced symptoms of inflammation, including inflammatory anemia, recruitment of neutrophils, liver apoptosis as well as increased pro-inflammatory serum cytokine levels.